Dukungan Keluarga dan Tingkat Kecemasan Pasien Pre Operasi di Ruang Rawat Inap (Studi Kasus RSU Proklamasi Karawang): Penelitian - Margarita Dewi Lelasari; Asep Paturohman; Siti Andayani (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Family support is important in care, especially for patients who will undergo surgery. This study is entitled "The Relationship Between Family Support and Preoperative Anxiety Levels of Patients in the Inpatient Room of Proklamasi Hospital, Karawang." The aim is to determine the relationship between family support and preoperative anxiety of patients. The method used is descriptive quantitative analysis with factor analysis using IBM SPSS 22.0. The results show that almost half of the patients are aged 20–35 years (42.1%), gender is balanced (50%), the majority have a high school education/equivalent (55.3%), and work as students (39.5%). Family support is mostly lacking (65.8%), while the level of preoperative anxiety of patients is mostly moderate (65.8%). The chi-square test shows a significance of <0.001, indicating a significant relationship between family support and patient anxiety.